Empowerment Of Pospaud Cades In Management Of Posture "Melati" Cepoko Gunungpati Semarang - Ari Yuniastuti (Jurnal Berkarya Pengabdian Masyarakat, 2019)
PosPAUD is a form of early childhood education services (PAUD) whose implementation is integrated with the services of Bina Keluarga Balita (BKB) and Posyandu. PosPAUD "Melati" is one of the PAUD Posts in Gunungpati Subdistrict. Based on PosPAUD data "Melati" Getas Cepoko village, the number of children active in PosPAUD aged 0-6 years in 2017 reached 25 children, while in 2018 active PAUD students were 18 people, there was a decrease in the number of community participation in PAUD activities. Likewise in the Posyandu activities which are held routinely on Saturdays on the first week of each month, the longer the number of people who come there is less The main problems faced by this pospaud include the limited number of cadres, the low knowledge and skills of cadres about nutrition and health and nutritional supplementary feeding (PMT) based on local food ingredients, the limited facilities available, the lack of knowledge about administrative order and active-creative learning. Community service methods are applied through pospaud cadre training, and assistance in the implementation of pospaud. Pospaud cadre empowerment activities carried out for 4 months, contributed 1). Increased cadre knowledge in managing PosPAUD; 2) Posyandu cadre skills in providing counseling and counseling about nutrition and health to children participating in PosPAUD and mothers of children under five; 3) Increased knowledge of PosPAUD cadres about nutritional supplementary feeding (PMT) based on local food ingredients; 4) PosPAUD cadre skills in making PMT (Supplementary Feeding) increased, and cadres could innovate types of PMT based on local food ingredients; 5) PosPAUD room is more comfortable and attractive; 6) Establishment of Family Medicine Park (TOGA). The results of the posyandu cadre empowerment activities showed an average initial knowledge of posyandu cadres on various aspects of being cured by 40.45%; the average posyandu cadre final knowledge on various aspects of being educated and trained is 95.25%; thus increasing the final evaluation results by 54.80% (classified in the medium category). The equipment assistance provided is able to support the smooth operation of the Melati pospaud activities. Keyword : pospaud, nutrition, supplmenetray feeding